DFT Study, POM Analyses and Molecular Docking of Novel Oxazaphosphinanes: Identification of Antifungal Pharmacophore Site - Khadidja Otmane Rachedi; Rania Bahadi; Mohamed Aissaoui; Taibi Ben Hadda; Billel Belhani; Abdeslem Bouzina; Malika Berredjem (Universitas Gadjah Mada, 2020)
A computational Petra/Osiris/Molinspiration/DFT(POM/DFT) based model has been developed for the identification of physico-chemical parameters governing the bioactivity of series of oxazaphosphinanes derivatives 1a-1f containing potential antifungal O,N-pharmacophore. Molecular docking study was performed in order to evaluate synthesized compounds their possible antifungal properties and their interactions in the binding site. Molecular docking studies revealed that the compounds 1a-1f have the potential to become lead molecules in the drug discovery process. The six compounds 1a–1f analyzed here were previously synthesized by our group.